Development of an integrated platform for in vitro expansion and CRISPR-Cas9 gene editing of umbilical cord blood NK cells - CHI Xiaolin, YUN Shaowei, YAO Yao, RAO Shuquan (Jichu yixue yu linchuang)
Objective To establish an integrated feeder-free platform for in vitro expansion and gene editing to tackle the major challenges in clinical applications of cryopreserved primary human natural killer (NK) cells in terms of low expansion efficiency, technical difficulty in genetic modification and safety concerns. Methods A non-viral CRISPR-Cas9 ribonucleoprotein (RNP)-based multiplex gene editing system was developed through systematic optimization of culture medium and nucleofection conditions. Cell phenotype (CD56+CD3-), viability, editing efficiency, and tumor-killing activity were evaluated via flow cytometry and cytotoxicity assays. Results The number of NK cells achieved 5 000-fold expansion over 25 days while maintaining high purity (CD56+CD3- ＞95%) and viability (＞90%).Post-thawing viability (＞80%) and tumor-killing capacity were preserved.Cas9 RNP delivery enabled efficient dual knockout of NKG2A and CISH immune checkpoint genes (＞80%), significantly enhanced cytotoxicity against K562 tumor cells (P＜0.05). Conclusions Compared to viral vectors, the non-viral strategy eliminates genomic integration risks and reduces off-target effects. This result may provide a safe and efficient technical platform for clinical application of NK cell immunotherapy and potentially encourage application of multiplex gene editing in cancer therapy.